2022
DOI: 10.1111/jce.15580
|View full text |Cite
|
Sign up to set email alerts
|

Low left atrial appendage emptying velocity is a predictor of atrial fibrillation recurrence after catheter ablation

Abstract: Background Recurrence of atrial fibrillation (AF) after catheter ablation (CA) remains common and studies have shown about 5%–9% annual recurrence rate after CA. We sought to assess the echocardiogram derived left atrial appendage (LAA) emptying velocity as a predictor of AF recurrence after CA. Objective To determine if LAA emptying is a marker of recurrence of AF post‐CA Methods A total of 303 consecutive patients who underwent CA for AF between 2014 and 2020 were included. Baseline clinical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Most previous studies investigating the association between LAA flow velocity and AF recurrence after radiofrequency catheter ablation (CA) focused on persistent AF or all types of AF patients, and many had a small sample size with limited follow‐up duration 7,13–18 . In contrast, our prospective study measured LAAeV and LAAfV on transesophageal echocardiography (TEE) before ablation for consecutive patients with PAF, which could avoid selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies investigating the association between LAA flow velocity and AF recurrence after radiofrequency catheter ablation (CA) focused on persistent AF or all types of AF patients, and many had a small sample size with limited follow‐up duration 7,13–18 . In contrast, our prospective study measured LAAeV and LAAfV on transesophageal echocardiography (TEE) before ablation for consecutive patients with PAF, which could avoid selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that high LAA flow velocity identifies AF lasting >48 h and <1 year patients with greater likelihood of remaining in sinus rhythm for 1 year after successful electrical or pharmacologic cardioversion 5 . A few recent studies found that a decrease in LAA flow velocity not only predicts embolic events but is also associated with AF relapse after CA 6–8 . However, the role of LAA flow velocity in predicting long‐term recurrence of AF ablation remains controversial based on limited studies, and another study failed to show the favorable results 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LA size increases and LA voltages decrease due to LA remodeling, which are considered the surrogate for LA fibrosis and the significant predictor of AF recurrence after CA ( 45 , 46 ). According to recent research, LAAFV is positively correlated with LA voltage and negatively correlated with LA volume ( 47 , 48 ). As an indicator reflecting LA contractile and reserve function, LAAFV demonstrates the severity of LA functional remodeling, which may occur in the early stage of LA remodeling ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters have been proposed to select patients who truly require an ablation strategy beyond PVI. [9][10][11][12][13] Unfortunately, none of these parameters have successfully identified these patients so far.…”
Section: Introductionmentioning
confidence: 99%